Loss and Gain in the Translation of Beatrix Potter’s The Tale of Peter Rabbit from English into Indonesian: Kehilangan dan Penambahan dalam Terjemahan The Tale of Peter Rabbit karya Beatrix Potter dari Bahasa Inggris ke Bahasa Indonesia - Nurkholidah, Endang Siti (Journal of Society and Development, 2025)
Trying to translate children’s story is not easy. Thus, to make children understand the translated text, the translator should really find the understandable word for children in the target language. Not only that, the translator also should be able to fix and match the culture of the target language as well as linguistics and extra-linguistics of the target language. Regarding that, this study intends to know the level of loss and gain in translation of the children’s story book entitled The Tale of Peter Rabbit written by Beatrix Potter who was known as English Writer for children's books featuring animals. Thus, the story of Indonesian version which has translated by Yulie Dhaniaty was also presented. Dealing with this study, in this case, there are three levels of loss and gain in translation: the level of word, phrase, and clause. Hence, those three levels are analyzed in both English and Indonesian versions. To do this study, the qualitative method is used. There are some steps of analyzing data, firstly, the text of the story in both English and Indonesian versions is read by the researcher. Then, the level of loss and gain in translation of the story is analyzed. Hence, the results show that the gain process is the dominant one. Thus, the loss in translation is also shown in some events of the story. From those results, it is summed that the loss and gain occurred because the translator wants to make the story more natural, alive and meaningful.